The potential for education programmes to create awareness about climate change among youth: a study of climate change knowledge in small towns in Poland - Ciepiela Agnieszka Katarzyna; Wójtowicz-Wróbel Agnieszka; Wałaszek Monika; Hess Daniel Baldwin (Miscellanea Geographica: Regional Studies on Development, 2025)
A critical component of climate change mitigation policy is to develop a sense of responsibility for climate change in children and young people. This study assesses the level of awareness among young people in small towns regarding climate change. The study also explores whether local climate change programmes involve urban communities in educational activities related to climate change and if these programmes have a real impact on the climate change awareness of young people. The research reports on a survey questionnaire of 195 young people in three types of secondary schools in the small town of Staszów, Poland. Findings suggest that there is no correlation between the type of school and the level of climate change awareness. Additionally, the study found that young people have a high level of awareness regarding local environmental activities.